Jewish identities : fifty intellectuals answer Ben Gurion - Ben Rafael, Eliezer (Brill, 2002)
Ten years after the creation of the state of Israel, David Ben Gurion wrote to 50 of the best thinkers and researchers in the world asking "Who is a Jew?" This publication contains the letters that answered this question, the original text of Ben Gurion, and an analysis by Shalow Tasavi.